The Serving Leader - "Jennings, Ken (Kenneth R.)"; "Stahl-Wert, John." ("San Francisco, California :")
Originally published: 2003. Includes bibliographical references (p. 117-122).
Keywords: LEADERSHIP.;LEADERSHIP -- MORAL AND ETHICAL ASPECTS.;LEADERSHIP -- FICTION